TRANSFORMATION OF INDONESIAN CITIES: HISTORY CHALLENGES AND EXPECTATIONS - Hardiyansyah, Muhammad Ricky; Nababan, Surya Aymanda (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
This research discusses the transformation of cities in Indonesia, covering the history, challenges, and expectations of the future, focusing on five major cities: Jakarta, Surabaya, Yogyakarta, Semarang, and Bandung. Using a qualitative descriptive approach, data were obtained through in-depth interviews, field observations, and documentation studies. The results of the study show that the history of the development of cities in Indonesia is influenced by colonialism, which forms spatial patterns and social segregation. Rapid urbanization, traffic congestion, air pollution, the impact of climate change, and social inequality are the main challenges faced. Nevertheless, various initiatives have been carried out, such as the implementation of the smart city concept in Bandung and Makassar, the management of green open spaces in Surabaya, and the preservation of local culture in Yogyakarta. However, community involvement in urban planning is still low, so the success of the initiative is not fully optimal. This research emphasizes the need for a holistic approach that integrates environmental sustainability, technology, cultural preservation, and community participation to realize inclusive and resilient cities. In conclusion, the transformation of cities in Indonesia requires the collaboration of all parties to face future challenges and create livable, sustainable, and competitive urban environments.